Palaeoeskimo structures in the Okak region of Labrador - Cox, Steven (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2003)
AbstractArchaeological research in northern Labrador over the past three decades has uncovered numerous Palaeoeskimo habitation structures with axial or mid-passage features. Such structures span both the Early Palaeoeskimo (Pre-Dorset and Groswater phase) and Late Palaeoeskimo (Dorset) periods. In Early Palaeoeskimo axial tent structures, the mid-passage apparently divides gender-based activity areas, but evidence for this is lacking in Dorset. This paper summarizes evidence for axial structures from much of the span of Palaeoeskimo in the Okak region of north-central Labrador.